 By Dileepkumar R

Similar education & reference books

The Story of the H.L. Hunley and Queenie's Coin

Through the Civil battle, Union forces blockade the port of Charleston so the accomplice military seeks how to assault the yank ships. George Dixon is a part of the crowd of fellows given the duty of making and development the "fish boat," a submarine. The H. L. Hunley finally units out on its challenge to sink Yankee ships, yet fails to come, its whereabouts unknown.

How to Write a Business Letter

Presents directions on the right way to write a company letter.

How to Write a Thank-You Letter

The best way to write the fitting thank-you notice.

Extra info for Arithmetic Graphs

Example text

3 It seems a hard problem to determine in general the full range of values of k and d and possible partitions (k1 , k2 ) of k, 0 ≤ k1 < k2 , with k2 − k1 = rd and r < a such that Ca,b , 2 ≤ a ≤ b, has a (k, d)-arithmetic numbering f for which k1 , k2 ∈ f (Ca,b ). In particular, if (a, b, k, d)=(a, b, a, 1) then for the partition (0, a) of a, since 1 | (a − 0) and r=a, we see that Ca,b a ≤ b, has an (a, 1)-arithmetic numbering f with 0, a ∈ f (Ca,b ). 7. 7 Every caterpillar is sequential. 2, any balanced bipartite graph G with {A, B}, | A |= a ≤ b =| B |, has a (k, d)-arithmetic numbering f with k1 , k2 ∈ f (G).

Let P be a parallel transformation of T that contains P1 as one of the constituent ept’s. Since vi+t vj−t is an edge in the path P(T) it follows that i+t+1=j-t ⇒ j = i + 2t + 1. The value of the edge vi vj is f + (vi vj ) = f + (vi vi+2t+1 ) = f (vi ) + f (vi+2t+1 ) If i is odd and 1 ≤ i ≤ n, then d + k + (q − 1)d + f (vi ) + f (vi+2t+1 ) = (i−2) 2 (i+2t+1−2) 2 (5) d = k + (q − 1)d + (i + t − 1)d. If i is even and 2 ≤ i ≤ n, then f (vi ) + f (vi+2t+1 ) = k + (q − 1)d + (i−2) 2 d+ (i+2t+1−1) 2 = k + (q − 1)d + (i + t − 1)d 35 (6) d (7) Therefore, from (5), (6), (7), we get f + (vi vj ) = k + (q − 1)d + (i + t − 1)d ∀i, 1 ≤ i ≤ n (8) The value of the edge vi+t vj−t is f + (vi+t vj−t ) = f (vi+t ) + f (vj−t ) = f (vi+t ) + f (vi+t+1 ) If i+t is odd, then f (vi+t ) + f (vi+t+1 ) = (i+t−1) 2 d + k + (q − 1)d + (i+t+1−2) 2 d = k + (q − 1)d + (i + t − 1)d If i+t is even, then f (vi+t ) + f (vi+t+1 ) = (i+t+1−1) 2 d + k + (q − 1)d + (i+t−2) 2 (9) (10) d = k + (q − 1)d + (i + t − 1)d (11) Therefore, from (9), (10), (11), we get f + (vi+t vj−t ) = k + (q − 1)d + (i + t − 1)d (12) From (8) and(12), f + (vi vj ) = f + (vi+t vj−t ).

Combinatorics, 10, 2007, DS6. M and Shetty, Sudhakar, On Arithmetic Graphs, Indian J. , 33(8), 2002, 1275-1283.